Cross-mapping interactions between access to water and sanitation, human and economic development in the least developed countries - Tiron-Tudor, Adriana; Apostu, Simona Andreea; Socol, Adela; Ivan, Oana-Raluca (Frontiers in Environmental Science, 2025)
IntroductionExtensive research on human and economic development in the Least Developed Countries (LDC) signaled concerns about the critical barriers that impede sustainable growth in these nations. This study examines the dynamic relationship between the two indices of human development (Human Development Index and Human Assets Index) and the capacity of 22 LDCs, between 2003 and 2019, to attract FDI, the degree of urbanization, water and sanitation access, as well as fertility rate.MethodsThe methodological construct is based on panel VAR and Granger causality methods. By considering all variables endogenous and interdependent, a cross-sectional dimension is introduced. The lag length was found using the Akaike Information Criterion (AIC), the Bayesian Information Criterion (BIC), and the Hannan-Quinn Information Criterion (HQIC). To analyse the changing relationship between variables, we used the 7-variable panel VAR for impulse response function analysis.Results and discussionThe results show a strong cause-and-effect link between urbanization, access to sanitation, and human development. Subsidiary, human development, and water access affect the level of foreign investments. The findings have practical implications for LDC governments by revealing a possible pathway for the sustainable development of the region. The provision of water access and sanitation infrastructure are investments that positively affect economic growth and human development. The paper emphasized the importance of equal and non-discriminatory access to water and sanitation services, an objective otherwise configured in SDG 6 “Clean water and sanitation”. Countries’ higher levels of human development are linked to more people living in cities, as they lead to more social and economic progress. Research examining how investments, access to water and sanitation, and birth rates affect human development supports this. The mechanisms of such interaction reside in higher income levels in urban areas, employment opportunities, and increased access to educational and health services.